2012
DOI: 10.1074/jbc.m112.412932
|View full text |Cite
|
Sign up to set email alerts
|

S-Adenosylmethionine-dependent Protein Methylation Is Required for Expression of Selenoprotein P and Gluconeogenic Enzymes in HepG2 Human Hepatocytes

Abstract: Background: Protein methylation is required for gluconeogenic enzyme expression. Selenoprotein P is transcriptionally controlled similarly to gluconeogenenic enzymes. S-adenosylhomocysteine is an inhibitor of methylation. Results: S-Adenosylhomocysteine decreases selenoprotein P and gluconeogenic enzyme expression. Conclusion: Hepatocellular methylation is a nexus of control over selenoprotein P and gluconeogenic enzyme expression. Significance: Determination of how methylation affects proteins involved in typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 44 publications
(58 reference statements)
3
19
0
Order By: Relevance
“…1,2 In this role, SAM is also involved in metabolic process regulation through contributing to nucleic acid 3 and protein methylation reactions. 4,5 In a different role, SAM is found as a central cofactor or cosubstrate in the enzyme family of radical SAM enzymes. 6 These enzymes catalyse a broad set of radical reactions, from C-C bond formations, [7][8][9] to complex skeleton rearrangements [10][11][12][13][14] (see also Ref 15 for an extensive review and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In this role, SAM is also involved in metabolic process regulation through contributing to nucleic acid 3 and protein methylation reactions. 4,5 In a different role, SAM is found as a central cofactor or cosubstrate in the enzyme family of radical SAM enzymes. 6 These enzymes catalyse a broad set of radical reactions, from C-C bond formations, [7][8][9] to complex skeleton rearrangements [10][11][12][13][14] (see also Ref 15 for an extensive review and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…The association of arsenic metabolism with diabetes could also be related to one-carbon metabolism because S-adenosylmethionine (SAM) is the methyl donor for arsenic metabolism (24,64). Experimental evidence has shown that SAM plays an important role in lipogenesis and in the development of diabetes (26,65,66). An in vitro study in Caenorhabditis elegans, an experimental model for human diseases and metabolic pathways (67,68), found that the synthesis of SAM regulated the expression of genes required for adequate lipid metabolism (65).…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study in Caenorhabditis elegans, an experimental model for human diseases and metabolic pathways (67,68), found that the synthesis of SAM regulated the expression of genes required for adequate lipid metabolism (65). In HepG2 human hepatocytes, the optimal balance between SAM and S-adenosylhomocysteine is critical to maintain appropriate expression of gluconeogenic enzymes (66). In addition, in a cross-sectional study of 50-75-year-old adults from the Netherlands (n = 648), plasma SAM was positively associated with fat mass and truncal adiposity, although reverse causation could not be excluded (69).…”
Section: Discussionmentioning
confidence: 99%
“…In diabetic subjects, β-cell apoptosis seems to be more of a deciding factor than replication in controlling the cell mass compared with control subjects [38]. Selenoprotein (SelP), a secretory protein primarily produced by the liver and regulated similar to that of the gluconeogenic enzyme glucose 6-phosphatase [39], by concerted action of peroxisome proliferator-activated receptor co activator 1α (PPAR-1α) and the transcription hepatocyte nuclear factor-4α [40]. It has been shown a positive correlation between hepatic SelP mRNA levels and insulin resistance in humans, a long with a positive correlation between serum SelP levels and both fasting plasma glucose and hemoglobin A1C (HbA1c) levels.…”
Section: Selenium In T2d Pathogenesismentioning
confidence: 99%